1974
DOI: 10.1029/ja079i025p03671
|View full text |Cite
|
Sign up to set email alerts
|

Zodiacal light and the asteroid belt: The view from Pioneer 10

Abstract: Brightnesses measured by the Pioneer 10 imaging photopolarimeter in two regio,ns of sky were compared on sky maps at sun-spacecraft distances from 2.4 to 4.8 AU to determine the spatial extent of the zodiacal light. Data in the ecliptic at elongations greater than 90 ø show negligible contribution to the zodiacal light beyond 3.3 AU, the 2:1 Jupiter resonance. The zodiacal light brightness at 2.4 AU is less than 10% of that observed at I AU.The imaging photopolarimeters (IPP) on Pioneer 10 and 11 have provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 3 publications
4
29
0
Order By: Relevance
“…The Pioneer 10 measurements from 2.4 to 3.2 a.u. exhibit a factor of >25 decrease in the surface brightness of two survey regions19, both measured at >102°. The measurements beyond 3.25 a.u.…”
Section: Methodsmentioning
confidence: 94%
“…The Pioneer 10 measurements from 2.4 to 3.2 a.u. exhibit a factor of >25 decrease in the surface brightness of two survey regions19, both measured at >102°. The measurements beyond 3.25 a.u.…”
Section: Methodsmentioning
confidence: 94%
“…Using the Pioneer 10 IPP data collected at various heliocentric distances R, Hanner et al (1974) find that the ZL brightness is below the detectable level of the instrument when the spacecraft is at beyond R = 3.26 AU. Hence the data obtained at the larger distances are most suitable for an analyses of diffuse radiations outside the ZL clouds.…”
Section: Observations and Reductionsmentioning
confidence: 99%
“…This was done at heliocentric distances beyond 1.015 AU Hanner et al 1974). Early results suggested that observations of the same sky regions decreased in brightness with heliocentric distance R to ≈ 3.3 AU Hanner et al 1976), beyond which there was no observable change; i.e., the zodiacal light became vanishingly small compared to the background galactic light (i.e.…”
Section: Pioneer 10/11 Spaceborne Visual Photometrymentioning
confidence: 99%